Cyber-Nationalism in China: Challenging Western Media Portrayals of Internet censorship in China - Ferguson, Jonathan (Teknokultura. Revista de Cultura Digital y Movimientos Sociales, 2015)
Book review: Jiang, Y. (2012). Cyber-nationalism in China: Challenging Western media portrayals of internet censorship in China. University of Adelaide Press.
Keywords: cybernationalism; cyber-nationalism; China; censorship; freedom of speech; governmentality